Regarde-moi - Estrougo, Audrey; Petit, Bruno; Durringer, Xavier, 1963-; Gaumont (Firm) (S.l. : Gaumont International, 2007)
Over een Japanse dove fotograaf
Chronicles one day in the emotional life of a Parisian housing project. Its focus is a group of young people, each of whom tries in his own way to express deep feelings for someone else while simultaneously maintaining the hard emotional shells needed to survive in the mean streets.
Copyright Claimant: Gaumont, 7eme Apache Films. Date of Creation: 2007; Date of Publication: 2007-09-26; Registration Number / Date: PA0001601728 / 2008-05-23.
Camera, Guillaume Schiffman ; editor, Marie-Pierre Renaud ; music, Baptiste Charvey.
Emilie de Preissac, Terry Nimajimbe, Salomée Stévenin, Eye Haidara, Paco Boublard, Oumar Diaw, Lili Canobbio, Salome Stevenin, Jimmy Woha, Djena Tsimba.
In French.
Summary from Seattle Film WWW site, viewed May 6, 2009.
Not viewed.
Keywords: Teenagers -- France -- Paris -- Drama; Feature films; Fiction films; Coming-of-age films